Synergistic effect of combination deltamethrin and piperonyl butoxide on behavioral avoidance and mortality responses of Aedes aegypti L. - Paeporn, Pungasem; Sathantriphop, Sunaiyana; Thanispong, Kanutcharee; Ya-umphan, Phubeth; Mukkhun, Pongsakorn (Disease Control Journal, 2021)
This study investigated the effect of piperonyl butoxide (PBO) with deltamethrin against field-collected Aedes aegypti from Thung Song district, Nakhon Si Thammarat province and Muang district, Chai Nat province. The World Health Organization (WHO) contact susceptibility test for female adult mosquitoes to 0.03% deltamethrin impregnated papers showed that two field populations of Ae. aegypti had exhibited strong resistance to deltamethrin with 26.67% (Nakhon Si Thammarat) and 3.7% (Chai Nat) mortality. Synergistic efficacy of piperonyl butoxide (PBO) 4% combined with deltamethrin 0.03% against both field populations of insecticide-resistant Ae. aegypti showed an increase in mortality to 38.53% for Nakhon Si Thammarat and 59.26% for Chai Nat mosquitoes. Behavioral responses of a standard deltamethrin-susceptible laboratory strain (Bora Bora) and both field isolates of Ae. aegypti exposed to deltamethrin (0.02 g ai/m2) and deltamethrin (0.02 g ai/m2)+PBO (4%) were tested using an excito-repellency test system. Contact irritancy (excitation) escape responses for Nakhon Si Thammarat and Chai Nat mosquitoes to deltamethrin were 57.6 and 72.9%, respectively, while escape responses to deltamethrin+PBO were 63.3 and 71.7%, respectively. The Bora Bora strain also showed marked contact irritancy to deltamethrin and deltamethrin+PBO, 69.5 and 67.9% escape, respectively. There was no significant difference in escape responses to deltamethrin and deltamethrin+PBO among three different Ae. aegypti groups (log rank test, p>0.05). It was concluded that 4% PBO synergist could help improve the efficacy of deltamethrin against deltamethrin-resistant Ae. aegypti, but did not induce an increase of escape response in Ae. aegypti to deltamethrin.